Episodic Memory Dysfunction and Effective Connectivity in Adult Patients With Newly Diagnosed Nonlesional Temporal Lobe Epilepsy - Bakhtiari, Aftab; Bjørke, Agnes Balint; Larsson, Pål Gunnar; Olsen, Ketil Berg; Nævra, Marianne C. Johansen; Taubøll, Erik; Heuser, Kjell; Østby, Ylva (Frontiers in Neurology, 2022)
Objective: Epilepsy is associated with both changes in brain connectivity and memory function, usually studied in chronic patients. The aim of this study was to explore the presence of connectivity alterations measured by EEG in the parietofrontal network in patients with temporal lobe epilepsy (TLE), and to examine episodic memory, at the time point of diagnosis. Methods: The parietofrontal network of newly diagnosed TLE patients (N=21) was assessed through electroencephalography (EEG) effective connectivity and compared to that of matched controls (N=21). Further, we assessed phenomenological aspects of episodic memory, in addition to verbal and visual memory functions. Lastly, we discuss the challenges regarding interpretation and the potential link between effective connectivity measures and neuropsychological memory scores. Results: Patients with TLE displayed decreased episodic (p = <0.001) and visual (p = 0.017) but not verbal (p=0.18) memory scores compared to controls at the time point of diagnosis. The patients showed a decreased right parietofrontal connectivity (p = 0.03) compared to controls, and significantly weaker connectivity in their right compared to their left hemisphere (p = 0.008). Conclusions: We found both changes in memory function and connectivity at the time point of diagnosis, supporting the notion that TLE involves complex memory functions and brain networks beyond the seizure focus to strongly interconnected brain regions, already early in the disease course.